Deflacyjne (redukcyjne) koncepcje przedmiotów fikcyjnych. Przegląd i analiza - Gurczyński, Jacek (Filozofia Nauki, 2011)
The objective of this paper is to discuss current reductive theories of the nonexistent objects, specifically — contemporary deflationary theories of the fictional objects. By such theories I mean those denying that fictional objects have any ontological status at all. Theories, which claim that fictional proper names denote some sort of objects but deny that these names denote individual objects, are treated as the reductive theories of non-existent as well. In the discourse I present the following ideas: 1) Russell’s theory of description with the further remarks by W. V. O. Quine; 2) A. Plantinga’s view that the fictional names have no denotation, which is realized in the framework of possible worlds semantics; 3) Theories by N. Wolterstorf and P. van Inwagen which can be seen as a link between strictly deflationary theories and meinongian theories; Wolterstorff claim that empty names denote general abstract objects and Inwagen identify fictional objects with theoretical objects of literal criticism; 4) Theories based on the speech acts theories; 5) Theories which identify fictional objects with mental objects. The conclusion of the argument is that the aforementioned theories are not adequate for the analysis of fiction (non-existent) and that more suitable for such a purpose are meinongian theories of non-existent objects.